Laboratory Diagnostics Performance in Uganda: A Survey of Test Availability and Constraints Across 100 Laboratories - Namuhani, Noel; Kiwanuka, Suzanne N.; Akulume, Martha; Kalyesubula, Simeon; Bazeyo, William; Kisakye, Angela N. (Research Square, 2021)
Clinical laboratory services are a critical component of the health system for effective disease diagnosis, treatment, control and prevention. However, many laboratories in Sub Saharan Africa remain dysfunctional. The high costs of tests in the private sector also remain a hindrance to accessing testing services. This study aimed at assessing the functionality of laboratories based on test menus and the associated constraints in Uganda. Methods This cross sectional quantitative study involved an assessment of 100 laboratories randomly selected in 20 districts from four regions of the country. Sixteen percent of the studied laboratories were regional hub laboratories. Laboratory in charges and managers in each of the selected laboratories were interviewed. A checklist for laboratory supplies adapted from the Essential Medicines and Health supplies list for Uganda, (2012) was used to assess availability of testing supplies. Data was analyzed using excel and STATA 14. Results At the point of assessment, generally, all laboratories were able to perform malaria tests and HIV tests. All the hub laboratories conducted malaria tests and TB screening. Less than half had electrolytes tests due to lack of equipment, nonfunctioning equipment and lack of reagents. Full blood count tests were missing in 25% of the hub laboratories mainly due to lack of equipment. The lack of reagents (66.7%) and the lack of equipment (58.3%) caused the majority 10/16 of the hubs to routinely referred specimens for tests that are supposed to be carried out in these laboratories due to lack of reagents (66.7%) and non-functional equipment (58.3%). Although officially recognized as an operational structure, Hub laboratories lacked a list of essential and vital supplies. Conclusions Most laboratories performed well for the common tests. However, many laboratories did not meet testing requirements especially for the advanced tests according to standard testing menus for Uganda due to non-functioning equipment, lack of equipment and reagents. Hubs lack list of essential supplies. Therefore, there is need to provide equipment to laboratories, repair the non-functional ones and develop an essential list of supplies for the hub laboratories.
Keywords: Functionality; Test menus; Supplies; Laboratories; Hubs; Uganda